E-Learning of Arabic Language (ELAL) using flipped learning model / Mohd Firdausi Idris - Idris, Mohd Firdausi (2022)
E-learning is a transition from traditional education or training to a more individualized and flexible education system based on information and communication technology. Since nowadays all over the world were still facing the pandemic COVID19 that make people cannot go anywhere as usual because for their safety. The purpose of this project is to develop the e-learning of Arabic language (ELAL) using the flipped learning model. Flipped Learning is a pedagogical technique that replaces traditional methods of teaching in a group setting with personalised education in an individual setting results in an engaging, dynamic learning environment where the educator helps students apply ideas and have fun with the subject matter. By this ELAL people can learning Arabic language at any time, and anywhere. The development process will be derived from the adapted waterfall model. The adapted waterfall model is a guide to creating an effective design that is widely used in the instructional design profession. This model provides a method for instructional designers, content developers, and even instructors to use the adapted waterfall model's procedures to build an efficient and successful teaching design for any instructional product. The project has been testing by using three test cases which is for admin, teacher, and student. The project testing is conducted to evaluate the functionality of the system in the development process to makes sure all the buttons are well functioning. This project can further improved from time to time.